PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN JASA YANG TERDAFTAR DI BEJ SEBELUM DAN SELAMA KRISIS MONETER - Andian Ari Istiningrum (Jurnal Pendidikan Akuntansi Indonesia, 2005)
This research has a purpose to compare and analyze the effects of monetary crisis to the financial performance of service companies. The financial performance was indicated by some financial ratios. These financial ratios include current ratio, total assets turnover, total liabilities to total assets, debt to equity, net profit margin, return on assets and return on equity. Research samples were 41 service companies. The analysis used wilcoxon signed rank test to compare the value of financial ratios between the period before and during  monetary crisis. The result showed that monetary crisis influenced almost financial ratios, except total assets turnover and debt to equity.  The differences of almost financial ratios between the period before and during monetary crisis is primary caused by the increasing of Rupiah to US Dollars